„Wahrheit kann nicht bestehen, wenn sie nur im Subjekte gemacht wird“. Bemerkungen zum Problem von Wissen und Glauben bei Kant - Nowikow, Igor (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2010)
The subject of the article is the problem of knowledge and faith in the philosophy of Immanuel Kant, and its aim is to discuss the polemics against the views of this philosopher from a realistic position. Firstly, the author believes that the whole philosophy of Kant has a subjective character and this subjectivism manifests itself in both the sphere of knowledge and the sphere of faith. According to the author this fact means a serious threat to the idea of truth. Secondly, the author is of the opinion that the philosophy of Kant can not solve the problem of the fusion of knowledge and faith into a single harmonic totality. It is above all the abstract rationalism of Kant that is exceedingly doubtful and that is expressed in the absence of connections between ethics and religion on one hand and the visible world on the other hand. The problem of subjectivism and the problem of knowledge and faith suggest taking a look at a wider ideological-historical context. Hence the theology – both the protestant and the catholic one – was considered in the article, and the author takes the line that the philosophy of Kant is more that of a child of German Protestantism and Martin Luther’s theology than that of a child of catholic theology.
Keywords: Metaphysics; Religion; Knowledge; Faith; Truth